Solvent Optimization for Extraction Mesua ferrea L. Leaves As An Antioxidant Using Simplex Lattice Design Method - Muliasari, Handa; Putu Intan Paramitha Sari, Luh; Hakim, Aliefman (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2022)
Mesua ferrea L. leaves methanol extract has the highest antioxidant activity than the other part of the plant. However methanol is toxic solvent, so the using of methanol for extraction may harmful for health and environment. The purpose of this study was to optimize the solvent combination of ethanol and water for extraction of Mesua ferrea L. leaves by using Simplex Lattice Design (SLD) method. The samples were extracted by Ultrasonic Assisted Extraction (UAE) using variation of solvents ethanol 96%, ethanol 50% and water. The solvent combination was optimized by using SLD method based on the Total Phenolic Content of all crude extract. The result showed that the TPC of ethanol 96%, ethanol 50% and water crude extracts were 574.7±66.97 mgGAE/g, 657.8±37.02 mgGAE/g and 524.23±14.48 mgGAE/g respectively. SLD was calculated and the optimal solvent obtained was ethanol 55% with TPC of 626.235± 23 mgGAE/g. The ethanol 55% extract of Mesua ferrea L. leaves has strong antioxidant activity (IC50 57.77) ppm using DPPH method.